Undergraduate Research: The Initiative, Trend and Reform - Syed Z A Shah, Ikram Din Ujjan, M. Kashif Shaikh, Naveed A. Lashar, Muzaffar A. Shaikh, M. Khalid Sheikh, Nida Batool, Kanwal (Pakistan Journal of Medical & Health Sciences, 2022)
The research isn’t finished until published while the students must actively engage in all facets of scientific and professional culture.1This implies they must comprehend the profession’s ideals while the students are taught the value of study, many fail to realize that study is not finished until it is printed.2 Releasing, peer review, and prioritization are all values of researchers that are not taught in textbooks, typical laboratories, or mass lectures.3 Students are sometimes included as co-authors in professional publications, although they are usually acknowledged. Rarely do students actively participate in both writing and peer review while the peer review and publishing will not be typical expectations of these essential encounters until then4.